2019
DOI: 10.1039/c8ta11587g
|View full text |Cite
|
Sign up to set email alerts
|

A robust and stretchable cross-linked rubber network with recyclable and self-healable capabilities based on dynamic covalent bonds

Abstract: Rubber composites composed of biobased epoxidized natural rubber and tunicate cellulose nanocrystals exhibited recyclable and self-healable capacities via transesterification reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
128
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(131 citation statements)
references
References 47 publications
3
128
0
Order By: Relevance
“…It was reported that dynamic ester linkages with reversible exchange reactions are capable of rearranging the topology network structure under appropriate conditions. 36,37 Thus, we envisaged the cured XNBR/ENR elastomers, comprising bhydroxyl ester linkages, are able to rearrange the topological structure via the transesterication reaction (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that dynamic ester linkages with reversible exchange reactions are capable of rearranging the topology network structure under appropriate conditions. 36,37 Thus, we envisaged the cured XNBR/ENR elastomers, comprising bhydroxyl ester linkages, are able to rearrange the topological structure via the transesterication reaction (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…In many reported studies, materials reprocessing usually takes place with the help of an external stimulus such as UV irradiation 34,35 or heating at high temperature, 36 or in the pres-ence of a catalyst. 27,37 Distinguished from other materials, sulfur-containing moieties (S-S) offer unique opportunities in which exchange can be activated at moderate temperature without any catalyst or initiator. 32,[38][39][40] Inspired by the strategy of importing exchange bonds from the hardener structure, we used disulfide-containing acids as crosslinkers to design biobased thermosets with dual dynamic exchange: through (i) carboxylate transesterification, and (ii) disulfide metathesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that catalyst type and concentration influence the T v , and several types have been introduced [4]. The most popular types are organic zinc salts, such as zinc acetylacetonate and zinc acetate [1,11,12]. The organic guanidine base 1,5,7-triazabicyclo[4.4.0]dec-5-ene is another effective transesterification catalyst, which has been often used in the design of epoxy-based vitrimeric systems [13,14].…”
Section: Introductionmentioning
confidence: 99%